Estudo do desempenho térmico e mecânico da argamassa geopolímérica a partir do metacaulim com adição de escória de alto forno - SILVA, Alan Rodrigo Palheta (2019)
The term Geopolimero was introduced from Davidovits, and indicates materials with chemical properties and raw materials of geological or mineral origin, so that the need for an alkaline medium, an aluminum and silicon to react and to form polymers occurs (from where the name Geopolimero ), calcium enters the interstice of the structure. Geopolymers are known for well-intentioned properties, such as curing, equal to or greater than Portland resistance, as well as reducing losses compared to traditional Portland Cements. In this work we aim to create a Geopolymer Mortar - AGP, and to find the best formulations and their main properties as kaolin raw material from the North Region and the High-EAF Slag Residue, the regression study of an EAF granulometry and a preliminary analysis. of Cement Paste Geopolimérico. A comparison was made in relation to the Common Refractory Mortar - ARC. The results were satisfactory, with an AGP having a resistance and a mean temperature of 400 ° C.